A complex grid investment decision method considering source-grid-load-storage integration - Zhang, Zheliang; Xia, Pei; Zhang, Xiaoxing (Frontiers in Energy Research, 2023)
First, the unilateral indexes of source, grid, load and storage in complex grids and the interactive indexes considering grid-source interaction, load-grid interaction, source-load interaction, source-storage interaction, load-storage interaction and grid-storage interaction are proposed to establish the investment decision indexes system. Then, a hesitance fuzzy linguistic term sets combined with regret theory is used to calculate the specific values of subjectivity indexes, taking into full consideration the regret avoidance and loss avoidance psychology of investors. In order to comprehensively consider the index preference of investors and the objectivity of weight assignment, a combined weighting method based on Analytic Network Process and Entropy Weight Method is obtained according to the game theory method. Finally, 16 projects to be built from each side of source-grid-load-storage were ranked for investment by a complex power grid investment decision method using the system of IEEE 39 nodes as an example to verify the effectiveness of the proposed method.